5b + 11 - 2b = 50
Bring all 'b' terms to one side
5b - 2b + 11 = 50
3b + 11 = 50
Thus the left side is simplified
2007-01-29 14:19:00
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
All they want you to do is collect like terms on the left side of the equation.
5b + 11 - 2b = 50
Like terms are 5b and -2b.
5b - 2b + 11 = 50
Take 2b from 5b.
3b + 11 = 50.
I guess they want you to stop here, since they tell you specifically not to solve.
2007-01-29 14:19:50
·
answer #2
·
answered by mirramai 3
·
0⤊
0⤋
You can only combine the like terms (having the same exact variable). So the 5b - 2b combine to be 3b
3b + 11 = 50
2007-01-29 14:20:24
·
answer #3
·
answered by hayharbr 7
·
0⤊
0⤋
5b + 11 - 2b = 50, combine like terms (5b and -2b)
3b +11 = 50, subtract 11 from both sides:
3b+11-11 = 50-11
3b = 50-11
3b = 39, divide each side by 3
3b/3 = 39/3
b= 13
check your answer by substituting your answer back into the equation:
5(13) + 11 - 2(13) = 50
65+11-26 = 50
50 = 50, so this is the right answer
2007-01-29 14:22:09
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
5b - 2b + 11 = 50
3b +11 = 50
Is this as far as they want you to go?
2007-01-29 14:21:01
·
answer #5
·
answered by Dennis H 4
·
0⤊
0⤋
combine like terms on the left side of the equation
5b-2b=3b
3b+11=50 is the simplified left side of the equation
2007-01-29 14:18:33
·
answer #6
·
answered by π∑∞∫questionqueen 3
·
0⤊
0⤋
First: combine "like" terms on the left side...
5b - 2b + 11 = 50
3b + 11 = 50
Sec: combine "like" terms > subtract "11" from both sides...
3b + 11 - 11 = 50 - 11
3b = 39
Third: isolate "b" on one side-divide both terms by "3"..
3b/3 = 39/3
b = 13
P.S. It needs to be solved!
2007-01-29 14:26:31
·
answer #7
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
5b + 11 - 2b = 50
3b + 11 = 50
3b = 39
b = 13
2007-01-29 14:19:37
·
answer #8
·
answered by 7
·
0⤊
0⤋
5b+11-2b=50
5b+2b+11-2b+2b
3b+11=50
2007-01-29 14:20:43
·
answer #9
·
answered by ~Zaiyonna's Mommy~ 3
·
0⤊
0⤋
69!
2007-01-29 14:20:51
·
answer #10
·
answered by Fabulous Weapon 2
·
0⤊
2⤋